(untitled) (Journal of Economic Research & Business Administration, 2016)
Corporate Governance – is the management of organizational and legal registration of businesses, streamlining the organizational structure, the construction of inter-firm relationships within the company and in accordance with the objectives. The system management of the organization’s corporate culture plays an important role, as a strategic tool to orient the team to achieve their goals. Since the internal characteristics of the corporate culture is difficult measurable, an important issue and the urgent need is to create techniques that allow to identify the main parameters of the current state of corporate culture in the company and the possible directions of change.